Динаміка участі деревних інтродуцентів у композиціях рівнинно-пейзажного району Тростянецького парку - Medvedev, V.A.; Iljenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
In the article on the basis of long-term monitoring supervisions is analysed dynamics of participation of the aliens in the decorative groups of plain part of dendropark Trostjanets on frequency of their occurrence during 1949–2007. The comparative analysis of participation of aliensin forming of decorative groups of the closed spaces and glades is made.